Effects of sodium thiosulfate (Na2S2O3) during resuscitation from hemorrhagic shock in swine with preexisting atherosclerosis. (January 2020) - Datzmann, Thomas; Hoffmann, Andrea; McCook, Oscar; Merz, Tamara; Wachter, Ulrich; Preuss, Jonathan; Vettorazzi, Sabine; Calzia, Enrico; Gröger, Michael; Kohn, Fabian; Schmid, Andreas; Denoix, Nicole; et al.
Graphical abstract: Abstract: Controversial data are available on hydrogen sulfide (H2 S) during hemorrhage and resuscitation, depending on timing, dosing, mode of application, and the H2 S donor used. Sodium thiosulfate (Na2 S2 O3 ) is a recognized drug devoid of major side effects, which attenuated murine acute lung injury and cerebral ischemia/reperfusion injury. Therefore, we tested the hypothesis whether Na2 S2 O3 would mitigate organ dysfunction in porcine hemorrhage-and-resuscitation. We studied animals with pre-existing coronary artery disease because of the reduced coronary arterial expression of the H2 S producing enzyme cystathionine-γ-lyase (CSE) in this prospective, randomized, controlled, blinded experimental study. 20 anesthetized and instrumented pigs underwent 3 h of hemorrhage (removal of 30 % of the blood volume and subsequent titration of mean arterial pressure to 40 mmHg). Resuscitation (72 h) comprised re-transfusion of shed blood, crystalloids, and continuous i.v. norepinephrine. Animals randomly received vehicle or Na2 S2 O3 (0.1 g·kg -1  h -1 ) for 24 h. Before, at the end of and every 24 h after shock, hemodynamics, metabolism, blood gases, lung, heart, kidney, and liver function and injury were evaluated together with cytokines and parameters of oxidative and nitrosative stress. Immediate post mortem lung, kidney, heart, and liver specimen were analyzed for marker proteins of inflammation and oxidative and nitrosative stress and mitochondrial respiratory activity in the heart, kidney, and liver. Immuno-histochemical analysis comprised lung extra-vascular albumin accumulation, nitrotyrosine formation, and CSE and glucocorticoid receptor (GCR) expression. Na2 S2 O3 significantly attenuated shock-induced impairment of lung mechanics and gas exchange (plateau and positive end-expiratory pressure at 72 h p = 0.0006/p = 0.0264; Horovitz index at 48 h p = 0.0261), which coincided with a higher tissue GCR expression (p = 0.0415). During resuscitation from hemorrhagic shock Na2 S2 O3 attenuated shock-induced acute lung injury in co-morbid swine, most likely due to a GCR expression related mechanism.